Pengaruh Likuiditas Profitabilitas Dan Leverage Terhadap Kebijakan Dividen - Lailatul Maghfiroh; Muhammad Aufa (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the effect of liquidity, profitability and leverage on dividend policy. The sample in this study were companies listed in the LQ45 index listed on the Indonesia Stock Exchange during the 2019-2021 period using purposive sampling method and obtained 30 companies. This research uses multiple linear regression analysis techniques. The results of this study indicate that liquidity and leverage have no effect on dividend policy. Meanwhile, profitability has a significant effect on dividend policy. The coefficient of determination shows 19,5%. These results indicate the ability of the independent variables to explain the dependent variable while 80,5% is explained by other variables